Unit Cost Calculation for Low Calorie Diet Packages to Support the Nutrition Installation Entrepreneurship of UGM Academic Hospital - Pratiwi Dinia Sari (Academic Hospital Journal, 2021)
Background: Nowadays, people have the awareness to maintain weight and to eat healthy diet. However, people prioritize practicality in preparing food due to the limited ability to prepare healthy food. Nutrition Installation in Universitas Gadjah Mada Academic Hospital has the potential to become a profit center by developing an entrepreneurship sector, specifically by providing a healthy catering services. To organize a good healthy catering services, preparations need to be done, including those related to human resources, equipment, operating systems, and to-be-applied tariffs. Objective: The purpose of this study was to determine the unit cost of the low-calorie diet package, the product of the entrepreneurship sector of Nutrition Installation. Design: Descriptive research with quantitive approach. This research was held at the Nutrition Installation in UGM Academic Hospital from June to November 2019, with the research steps conducted: 1) Identifying the details of the low-calorie diet package, 2) Identifying the direct cost consisting of direct non-overhead cost and direct overhead cost, 3) Identifying the indirect cost, 4) Calculating the unit cost.  Results: The unit cost for a low-calorie diet package is IDR 70.553 per portion consisting of lunch, snack, assessment, and nutritional consultations per package.  Conclusions: The unit cost obtained from this study can be used as the basis to determine the tariff for the hospital’s Nutrition Installation’s healthy catering services.